Stakeholders’ Perspectives on the Philosophy of English Learning Curriculum Development - Sinaga, Irene Riskiana Vionauli; Ira Maisarah (English Lecturers and Teachers Association (ELTA), 2024)
The fundamental of human development, including the advancement of science, is philosophy. It is impossible to divorce the philosophical underpinnings of science's advancement from their integration into curricula. The purpose of this study is to look into how the philosophy of science is used in the curriculum development of English language instruction at Bengkulu City's Sint Carolus High School. This study used instruments of questionnaires and interviews, and a qualitative-descriptive methodology was employed, with Four internal school stakeholders serving as research subjects. The study's findings demonstrated the importance of a philosophical basis for curriculum building by fusing the Tarakanita Character Education formulation, the Pancasila philosophy, and the national curriculum. This curriculum's philosophical underpinnings have beneficial effects on educational institutions, particularly for those involved in creating and developing their curricula and making sure that the materials used are grounded in scientific theory. Keywords : Curriculum_development; Perspectives; Philosophy; Stakeholders